2016
DOI: 10.4314/sajg.v5i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating spectral indices for winter wheat health status monitoring in Bloemfontein using Lsat 8 data

Abstract: Monitoring wheat growth under different weather and ecological conditions is vital for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The presence of many downward "spikes" that exist below 40 Wh is indicative of cloud movement, which impacts severely on the yield of output power for all three tilt angles. Bloemfontein is a summer rainfall area with less cloud movement during the winter months [28]. This is confirmed in Figure 7 where only one significant downward "spike" is evident on 14 June 2016, with no other interruptions in direct beam radiation visible between 17 May and 23 July 2016.…”
Section: Resultsmentioning
confidence: 53%
“…The presence of many downward "spikes" that exist below 40 Wh is indicative of cloud movement, which impacts severely on the yield of output power for all three tilt angles. Bloemfontein is a summer rainfall area with less cloud movement during the winter months [28]. This is confirmed in Figure 7 where only one significant downward "spike" is evident on 14 June 2016, with no other interruptions in direct beam radiation visible between 17 May and 23 July 2016.…”
Section: Resultsmentioning
confidence: 53%
“…On the other hand, lower NDVI values may indicate weaker photosynthetic activity and overall poorer vegetation health, due to likely unfavorable growing conditions (e.g., water stress, exposure to herbicide). The NDVI is typically used as indicator to monitor ecosystem health (e.g., Bento et al 2018;Flores-Cardenas et al 2018;Mariano et al 2018) and crop phenology (e.g., Mashaba et al 2016;Martin and Latheef 2017;Inurreta-Aguirre et al 2018). A number of studies (e.g., Thelen et al 2004;Dicke et al 2012;Lewis et al 2014;Prakash et al 2017) have demonstrated that NDVI is an effective index in detecting herbicide damage on plants.…”
Section: Remote Sensing Datamentioning
confidence: 99%